A Study Of Association Of Intra-Abdominal Pressure With Severity And Outcome In Patients Of Emergency Laparotomy - Kurra, Amit; Sukhadia, Mukta; Thomas, Nimil Mary; Sethi, Deepak; Sharma, Navaratna (Journal of Society of Surgeons of Nepal, 2024)
Introduction: The present study is done to study the association of intra-abdominal pressure with intra-operative findings and postoperative surgical complications in patients of emergency laparotomies so that timely and appropriate interventions can be planned and administered. Methods: The study was done on 84 patients. The intra-abdominal pressure was measured indirectly by measuring the pressure within the urinary bladder via Foley's catheter. Results: There was positive association between the higher grades of IAP and intra-abdominal contamination and gangrenous bowel, the mean value of IAP being 20.4 mmHg. A statistically positive association was also observed between preoperative IAP and post-operative complications, the mean IAP ≥19mmHg. Conclusion: There is a significant positive association of raised pre-operative intra-abdominal pressure with intra-operative finding of gangrenous and edematous bowel and postoperative surgical complications.